2017
DOI: 10.1111/ipd.12295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salivary parameters in the caries development in orthodontic patients—an observational clinical study

Abstract: The present study demonstrated that saliva of individuals under orthodontic treatment is subjected to changes in properties that have implications on the onset of ACL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 26 publications
4
32
3
5
Order By: Relevance
“…The study results show that statistically significant difference occurred between the study and control groups of respondents (p = 0.001) in week 12 of the therapy, in regard to the saliva pH values (Table 4), which is consistent with results of some other studies [14,16]. Some studies found no changes in the saliva pH values during all three follow-up periods of patients with fixed orthodontic appliances [24].…”
Section: Discussionsupporting
confidence: 89%
“…The study results show that statistically significant difference occurred between the study and control groups of respondents (p = 0.001) in week 12 of the therapy, in regard to the saliva pH values (Table 4), which is consistent with results of some other studies [14,16]. Some studies found no changes in the saliva pH values during all three follow-up periods of patients with fixed orthodontic appliances [24].…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting to note that, as previously demonstrated by our group, the first clinical evidence of ACL was seen 3 months after the placement of orthodontic appliances (2). In line with these findings, this investigation pointed out that the deficiency in calcium concentration can be considered a risk factor (HR of 0.73) associated with ACL development in individuals submitted to orthodontic treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The research protocol considered the clinical assessment of dental caries (Nyvad index) and saliva collection. Detailed methodological aspects of this cohort and information regarding the appliances system have been published elsewhere (2). The sample size was estimated to test whether there is a difference in the mean of white spot lesions between individuals undergoing orthodontic treatment and those who were not submitted to it (baseline).…”
Section: -Study Design and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Las variaciones de los niveles de esta enzima producen cambios en los niveles salivales de fosfatos, lo que conduce a la iniciación y progresión de caries 41 . Algunos autores han reportado valores mayores de esta enzima en niños sin lesiones cariosas que en niños con caries activas 42,43 . En la saliva estimulada, el principal sistema regulador es el del ácido carbónico / bicarbonato; la secreción parotídea provee el bicarbonato responsable de restablecer el pH salival.…”
Section: A) Cariesunclassified